Study on Vulnerability of Malnourished Children To Urinary Tract Infection - Chowdhury, Bidhan Roy; Das, Suchanda (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Knowledge of baseline risk of urinary tract infection in malnourished child can help clinicians make informed diagnostic and therapeutic decisions. To see the prevalence of Urinary Tract Infection (UTI) in malnourished children & compare the prevalence of UTI between malnourished and well-nourished children. As well as to study the clinical features & to see organisms responsible for UTI and their antibiotic sensitivity patterns in malnourished children. Materials and methods: This prospective comparative study was carried out among fifty hospitalized malnourished children (Case) and fifty hospitalized well-nourished children (Control) during the period of July to December 2010. The relevant information from history and physical examination were noted in a preformed standard questionnaire. Laboratory investigations and other necessary tests were done as indicated. Clean-catch midstream urine samples were collected from all studied children in sterilized test tube and sent to laboratory within one hour of collection. Results: Prevalence of UTI in malnourished children was 16 percent, which was higher than those of control (4%), which was statistically significant. The prevalence of UTI in marasmic-kwashiorkor (66.67%) was much higher than those of kwashiorkor (5.26%) and marasmus (33.33%). Age and sex of the malnourished individuals did not contribute to the prevalence of UTI. Pyuria (Pus cell > 10/HPF) alone was not found to be diagnostic but had significant correlation with the presence of UTI. Symptoms and signs of UTI in malnourished children were scanty and not adequate for clinical suspicion. Organism responsible for UTI in malnourished children were E. coli (75.%) Proteus (12.5%) and Klebsiella (12.5%) which were almost sensitive to commonly used antibiotics, except amoxycillin. Conclusions: Prevalence of UTI is significantly high among malnourished children of all categories. But symptoms and signs of UTI are non-specific and scare in malnourished children. So, all malnourished children should be routinely investigated for UTI. JCMCTA 2018 ; 29 (1) : 57-62